2007
DOI: 10.1088/0029-5515/47/9/030
|View full text |Cite
|
Sign up to set email alerts
|

Fishbone instability excited by circulating electrons

Abstract: Fishbone instability excited by the supra-thermal circulating electrons in tokamaks is investigated. It is found for first time that the procession of all the circulating electrons is in ion diamagnetic direction if magnetic share is neglected. The circulating electrons, which experience both high field side and low field side, play bigger role on the modes than the barely trapped electrons. The analyses show that the mode frequency is close to the procession frequency of circulating electrons comparable with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…Equations (4) and (12) generalize the electron fishbone dispersion relations, analyzed recently [12,13,31], to both trapped and barely circulating fast particles, including (s, α) model equilibrium effects onω d . A detailed discussion of the circulating electron effect on δŴ k was recently given in [32]. A further extension of Eqs.…”
Section: Resonant Excitation By Trapped and Barely Circulating Supra-mentioning
confidence: 99%
See 2 more Smart Citations
“…Equations (4) and (12) generalize the electron fishbone dispersion relations, analyzed recently [12,13,31], to both trapped and barely circulating fast particles, including (s, α) model equilibrium effects onω d . A detailed discussion of the circulating electron effect on δŴ k was recently given in [32]. A further extension of Eqs.…”
Section: Resonant Excitation By Trapped and Barely Circulating Supra-mentioning
confidence: 99%
“…That δŴ k,N L is predominantly imaginary, as it emerges from comparisons of Eqs. (32) and (39), suggests that the nonlinear fishbone cycle is essentially determined by the fast particle scattering out of the resonant region. Given the fluctuation level of the mode, the nonlinear time scale, τ N L , as derived from Eq.…”
Section: Nonlinear Amplitude Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…The instability is thought to be excited by the barely trapped electrons (BTEs) [32] or the barely circulating electrons (BCEs) at the negative magnetic shear [36,37]. To identify the resonance conditions, hard x-ray detectors (CdTe) were used to measure the energetic electron spectra on HL-2A.…”
Section: Internal Kink Mode Driven By Energetic Electronsmentioning
confidence: 99%
“…It was then found that resonance can occur between circulating energetic ions and the kink modes [24][25]. On the other hand, energetic electrons have similar effects on kink modes due to drift-reversal for the barely trapped electrons or due to the negative magnetic shear for the passing particles [26][27][28][29]. Moreover, energetic electrons in the trapped-passing boundary are recently found to interact with a tearing mode leading to chirping-down of magnetic island rotation frequency in the lower collision region [30][31][32].…”
Section: Introductionmentioning
confidence: 99%